Simultaneous Temperature Measurements and Aerosol Collection During Vaping for the Analysis of Δ9-Tetrahydrocannabinol and Vitamin E Acetate Mixtures in Ceramic Coil Style Cartridges - Lynch, John; Lorenz, Lisa; Brueggemeyer, Jana L.; Lanzarotta, Adam; Falconer, Travis M.; Wilson, Robert A. (Frontiers in Chemistry, 2021)
Incidence of e-cigarette, or vaping, product use-associated lung injury (EVALI) has been linked to the vaping of tetrahydrocannabinol (THC) products to which vitamin E acetate (VEA) has been added. In this work we vaped THC/VEA mixtures at elevated power levels using a variety of ceramic coil vaping cartridges and a commercially available vaping device, while simultaneously measuring temperature and collecting the vaporized condensate. The collected vapor condensate was analyzed for evidence of VEA decomposition by GC/MS, GC/FT-IR/MS, and LC-APCI-HRMS/MS. Mean temperature maxima for all examined cartridges at the selected power exceeded 430℃, with a range of 375 to 569℃, well beyond that required for thermal decomposition of VEA. The percent recovery of VEA and Δ9-THC from the vaporized mixture in six cartridges ranged from 71.5 to 101% and from 56.4 to 88.0%, respectively. Analysis of the condensed vaporized material identified VEA decomposition products duroquinone (DQ), 1-pristene, and durohydroquinone monoacetate (DHQMA); a compound consistent with 4-acetoxy-2,3,5-trimethyl-6-methylene-2,4-cyclohexadienone (ATMMC) was also detected. The concentration of DQ produced from vaporization of the THC/VEA mixture in one cartridge was found to be 4.16 ± 0.07 μg per mg of vapor condensate.